Technique of revascularization in odontopediatria step by step. A case report - Patricia Blázquez Molina; María Fe Riolobos González (Asociación Latinoamericana de Odontopediatría, 2019)
Introduction: Revascularization is a current procedure for necrotic teeth with an immature apex; It is a more conservative clinical management option with respect to traditional apicoformation treatments, where, through the induction of the stem cells of the periapical dental papilla, a bleeding is created inside the root canal, which becomes a stable clot that allows the physiological radicular maturation, at the same time as the thickening of the duct walls. The objective of this treatment is to allow a complete closure of the apex. Clinical case: The case of a 7-year-old boy with apical abscess on tooth 21 is presented, a revascularization treatment is performed following the technique described by Hoshino (1996). Following the theory described by Iwaya in 2001, and Banchs and Trope in 2004, using bi-antibiotic paste in the revascularization, and mineral trioxide aggregate as a barrier between the clot and the final restoration. Conclusions: In the last published studies, calcium hydroxide and tri-antibiotic paste have been used as filling materials between phases, to use a bi-antibiotic mixture. Its effectiveness against calcium hydroxide alone has not been proven, which is used again as the only intermediate material between the steps of the revascularization treatment. With this technique we try to achieve a complete root development and thicker walls, thus avoiding the problem of root fracture.